PROVENANCE AND ALTERATION OF GLACIAL SEDIMENTS IN KING GEORGE ISLAND, ANTARCTICA - Gabrig Turbay Rangel, Caio Vinicius; D'Azeredo Orlando, Marcos Tadeu; Jardim, Hannah Almeida; Carreiro Almeida, Ivan Carlos; Mendonca, Eduardo De Sa; Teixeira, Daniel De Bortoli [UNESP]; Thomazini, Andre; Schaefer, Carlos Ernesto (Univ Estado Rio De Janeiro, Fac Geologia, 2019)
Mineralogical and geochemical data of glacial sediments of Low Head, King George Island, Antarctica, are presented to approach its provenance and alterations aspects. Mineralogical analyses were performed using petrography and an x-ray diffraction method, while to the geochemistry was performed by x-ray fluorescence. Comparisons using major elements in the sediments with possible source areas, suggested that they are closest to the King George Island parent rocks, with no contribution of rocks from Antarctic Peninsula. The gravel and sand fractions demonstrate that the till is composed of basaltic and andesitic rock fragments, plagioclase, pyroxene and amphibole, typical of active immature volcanic arc. The mud fraction indicates chemical characteristics consistent with calc-alkaline to tolleitic and metalluminous affinity of source rock of the till and the presence of secondary mineral phases, such as laumontite, brucite and saponite. The values of alteration indices, such as the chemical index of alteration (CIA) and the SiO2/Al2O3 ratio, in the regional rocks and sediments reflect a remarkable degree of alteration, possibly due to hydrothermal activity, exemplified by the presence of laumontite. In addition, bivariate chemical diagrams suggest slight weathering compared to the South Shetland Islands, which may have been responsible for the formation of brucite and saponite. The results suggest that although there are secondary mineral products, some grade of weathering could have acted in the till during sedimentary cycles or the till was strongly influenced by components of local weathered basalts.
Keywords: Sediment provenance; Alteration; Glaciogenic sediments; Mineralogy; Geochemistry